Perception of the new competition formats in the Innsbruck 2012 Youth Olympic Games sports programme - spectators` perspective - Schnitzer, M.; Scheiber, S.; Lang, M.; Brandstetter, E.; Kopp, M. (Sport Management Review, 2014)
The Youth Olympic Games (YOG) was initiated by the International Olympic Committee (IOC) in 2007 aiming to reach out to a younger target group. Besides the introduction of a Culture and Education Programme the creation of new competition formats was an important initiative. The objective of this study was to assess the spectators` perception of the new sports competitions at the first Winter YOG 2012 in Innsbruck, Austria. The aim was to understand how the Games were perceived by on-site spectators attending the event. For this purpose a quantitative research approach was chosen. Based on an extensive literature review a paper questionnaire was developed and distributed among the spectators during the YOG in Innsbruck. The results revealed that the Level of Performance was perceived very positively across all competitions. Regarding the Entertainment Value, Future Development, Eustress and Rules the spectators` perception differed between the various competitions. The findings from the study in hand provide important insights for future organisers of sports events and other related stakeholders (federations and sports clubs) with respect to the implementation of new sports competitions.